2022
DOI: 10.3390/cells11172711
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Cell Survey of Cellular Heterogeneity in Human Great Saphenous Veins

Abstract: Background: The great saphenous vein (GSV) is the most commonly used conduit for coronary arterial bypass graft. However, the status of the GSV, including metabolic dysfunction such as diabetes mellitus (DM) complication, is strongly associated with vein graft failure (VGF). To date, the molecular mechanism underlying VGF remains elusive. Detailed characterization of the cellular components and corresponding expression regulation in GSVs would be of great importance for clinical decision making to reduce VGF. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…This secretory population, characterized by high APOD expression, was also widely distributed throughout the wall ( Fig 4B , S8B Fig ). Lastly, a small ANGPTL7 + fibroblast population (284 cells; Fig 4A ) with potential pro-fibrotic effects [ 66 ] was detected in agreement with previous studies [ 6 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This secretory population, characterized by high APOD expression, was also widely distributed throughout the wall ( Fig 4B , S8B Fig ). Lastly, a small ANGPTL7 + fibroblast population (284 cells; Fig 4A ) with potential pro-fibrotic effects [ 66 ] was detected in agreement with previous studies [ 6 ].…”
Section: Resultssupporting
confidence: 89%
“…The proportion of ECs ranged from 7.8 to 10.1% across the 4 veins analyzed ( Fig 1C ), for a total of 1,695 cells out of 20,006 in the focused uniform manifold approximation and projection (UMAP) plot ( Fig 2A ). These subdivided into five groups corresponding to arteriovenous zonation phenotypes annotated elsewhere [ 6 , 28 30 ]: EC1 [arteriolar-like], 215 cells; EC2 [capillary-like], 400; EC3 [venous-like], 712; EC4 [valvular-like], 257; and EC5 [lymphatic-like], 111 ( Fig 2 ). Canonical markers in common among all EC subsets were CDH5 , CLDN5 , ERG , PECAM1 , and VWF ( Fig 1D ), while markers characterizing each population are presented in S3A Fig and Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Since the marker genes of pericytes and smooth muscle cells often overlap, and their expression patterns are tissue-specific, identifying suitable in vivo markers to accurately interpret transcriptional and phenotypic changes in these cell types is of utmost importance (Chasseigneaux et al, 2018, Kumar et al, 2017, Smyth et al, 2018. Recent studies have identified pericyte-specific markers in different tissues using single-cell RNA sequencing (Baek et al, 2022, Sun et al, 2022, enabling characterization of various cell types and their cell-cell communication. In this study, a single-cell transcriptome analysis was performed to examine the cellular heterogeneity in erectile dysfunction caused by diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the marker genes of pericytes and SMCs often overlap, and their expression patterns are tissue-specific, identifying suitable in vivo markers to accurately interpret transcriptional and phenotypic changes in these cell types is of utmost importance ( Chasseigneaux et al, 2018 ; Kumar et al, 2017 ; Smyth et al, 2018 ). Recent studies have identified pericyte-specific markers in different tissues using single-cell RNA sequencing ( Baek et al, 2022 ; Sun et al, 2022 ), enabling characterization of various cell types and their cell-cell communication. In this study, a single-cell transcriptome analysis was performed to examine the cellular heterogeneity in ED caused by diabetes.…”
Section: Introductionmentioning
confidence: 99%